Personal competency of Indonesian teacher certified - Yayan Sudrajat (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study was to analyze the competencies possessed by teachers certified by their competence of certified teachers. This study is a survey research with a descriptive approach. Source of research data include informants, documents, and events or activities. Informants consisting of principals, Indonesian Language teachers, and the students of SMA Bina Spora Mandiri. The technique of collecting data with observation, interviews, and reviewing documents. Observation data is a description of the factual, accurate, and detailed about the immediate circumstances, human activities, and social situations. Data were analyzed using analysis model, namely interaction with data reduction, display, and drawing conclusions. Data validation was done by using triangulation. One of the conclusions from this study is good personality of the teacher will give a good example to their students and communities so that teachers perform as a highly exemplary. Teachers as educators whose primary task of teaching have personality characteristics that influence the success of human resource development.